Structural Analysis of the Newly Prepared Ti55Al27Mo13 Alloy by Aluminothermic Reaction - Michna, Štefan; Svobodová, Jaroslava; Knaislová, Anna; Novotný, Jan; Michnová, Lenka (Materials, 2025)
This study presents the structural and compositional characterisation of a newly developed Ti55Al27Mo13 alloy synthesised via aluminothermic reaction. The alloy was designed to overcome the limitations of conventional processing routes for high–melting–point elements such as Ti and Mo, enabling the formation of a complex, multi–phase microstructure in a single high–temperature step. The aim was to develop and characterise a material with microstructural features expected to enhance wear resistance, oxidation behaviour, and thermal stability in future applications. The alloy is intended as a precursor for composite nanopowders and surface coatings applied to aluminium–, magnesium–, and iron–based substrates subjected to mechanical and thermal loading. Elemental analysis (XRF, EDS) confirmed the presence of Ti, Al, Mo, and minor elements such as Si, Fe, and C. Microstructural investigations using laser confocal and scanning electron microscopy revealed a heterogeneous structure comprising solid solutions, eutectic regions, and dispersed oxide and carbide phases. Notably, the alloy exhibits high hardness values, reaching >2400 HV in Al2O3 regions and ~1300 HV in Mo– and Si–enriched solid solutions. These results suggest the material’s substantial potential for protective surface engineering. Further tribological, thermal, and corrosion testing, conducted with meticulous attention to detail, will follow to validate its functional performance in target applications.